2021
DOI: 10.1177/00194662211063562
|View full text |Cite
|
Sign up to set email alerts
|

How Does Innovation Affect Economic Growth? Evidence from G20 Countries

Abstract: We study the interactions between innovation and economic growth in G20 countries over 1961–2019. We establish whether there is a temporal causality between these two variables. Employing the autoregressive distributive lag framework, our results expose a grid of short-run and long-run causal relationships between innovation and growth, including long-run unidirectional causality from innovation to economic growth. Overall, our findings shed light on the real effects of innovation on economic growth. JEL Code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…Zinātniskajā literatūrā ir izteikts viedoklis, ka pastāv ilgtermiņa cēloņsakarības starp ekonomisko izaugsmi un izmantotajām inovācijām, vienlaikus atzīstot, ka dažādās valstīs var būt dažādas stratēģijas, kurās jāņem vērā valsts perspektīvas un attīstības stratēģijas (Sarangi, K., Rudra, P., Tamal, N. & all, 2022). Inovatīva un ekoefektīva ekonomika ir viens no Latvijas ilgtspējīgas attīstības pīlāriem.…”
Section: New Challenges In Scienceunclassified
“…Zinātniskajā literatūrā ir izteikts viedoklis, ka pastāv ilgtermiņa cēloņsakarības starp ekonomisko izaugsmi un izmantotajām inovācijām, vienlaikus atzīstot, ka dažādās valstīs var būt dažādas stratēģijas, kurās jāņem vērā valsts perspektīvas un attīstības stratēģijas (Sarangi, K., Rudra, P., Tamal, N. & all, 2022). Inovatīva un ekoefektīva ekonomika ir viens no Latvijas ilgtspējīgas attīstības pīlāriem.…”
Section: New Challenges In Scienceunclassified
“…Job creation, income inequality, productivity, cultural and political consciousness, cultural attitude, choices facing people, welfare level of future generation, human capital in R & D, and well-functioning labor market [8]; [9]; [10]; [11]; [12]; [13]; [18] Organization level…”
Section: Individual Levelmentioning
confidence: 99%
“…Partnership between industry and educational institutions, R&D investment in high-tech industries, entrepreneurship in terms of new density and the potential of innovation, utilization of newly invented inputs, intellectual property right, patent application, patent-intensive industries, factor accumulation, and raising productivity, provision of good governance, and reassuring institutions, the endowment of information and communication technology (ICT), venture capital funding and stronger linkage and interface between publicly funded research institutes and private companies, the importance of competition and firm entry and exit barriers, well-functioning financial market, production, marketing, and customer acquisition and customer satisfaction of firms, capital accumulation, international competitiveness, quality of scientific research organization, trade volume, barriers to entry (Market Accessibility) [8]; [14]; [9]; [16]; [17]; [12]; [18]; [1]; [19]; [13]; [20]; [21]; [15] Environmental level Physical environment: Use of natural resources, renewable energy use, CO2 emission, environmental protection, green economic development, ecological footprint Social Environment: Culture, and religious belief, social and environmental condition, solid political stability [2]; [21]; [16]; [22]; [23]; [24]; [13] The review of literature explored three scopes of the possible impacts of technological innovation. It was found that through the individual, organizational, and environmental levels TI can impact an economy.…”
Section: Individual Levelmentioning
confidence: 99%
See 2 more Smart Citations